Method of synthesis of nonlinear qualitative regulators - Антонов, В. К.; лазок, О. М. (Proceedings of National Aviation University (archive), 2003)
The new method of synthesis of regulators for nonlinear dynamic objects is offered. The task of synthesis is solved by the modified method of analytical constructing on the basis of a square-law functional of quality. The method is constructed on the basis of the sequential taking into account nonlinear terms in the object model and appropriate extension of the Bellman function. For its additional terms the damping factors are entered which determine operation speed